Review on Utilization of Visual Basic Software for Improving Students’ Computer Programming Performances - Gatchalian, Chuckee B.; Handig, Joy Edilaine R.; Baluyot, Fioglo (Bumi Publikasi Nusantara, 2024)
The main objective of this study is to review on utilization of visual basic software for improving students’ computer ability. This study is a literature survey. We focused on two aspects: (i) utilization of visual basic software and (ii) computer programming performance. This study provided important information and benefits to the school, administrators, teachers, students, and researchers.